Imbalance of T cell subsets: a core event that mediates the progression of T2DM and its complications - Xie, Xiang; Li, Fan; Wu, Qian; Zeng, Chunlan; Chen, Xi; Wang, Wenwen; Zhang, Chunxiang; Chen, Huan (Frontiers in Immunology, 2025)
Type 2 diabetes mellitus poses a substantial global health burden, increasing evidence highlights the critical role of T cells in promoting T2DM progression. This review provides an overview of the mechanisms by which specific T cell subsets drive T2DM pathogenesis and its complications, while also highlighting emerging immunotherapeutic strategies. Preceding overt T2DM, T cells infiltrate insulin-sensitive tissues early, and a skewing of T cell subsets toward pro-inflammatory phenotypes leads to an imbalance that fosters inflammation and M1 macrophage polarization, driving the development of T2DM. In addition, this T cell subset imbalance contributes to disease progression by inducing insulin resistance and β-cell dysfunction. As T2DM progresses, the T cell subset imbalance and their tissue infiltration extend to the cardiovascular system, kidneys, retina, brain, and peripheral tissues—contributing to diabetic complications such as atherosclerosis, diabetic kidney disease, diabetic retinopathy, Alzheimer’s disease, and diabetic foot ulcers. The evidence summarized in this review underscores the central role of T cell subset imbalance in the progression of T2DM and its associated complications. Building on these findings, we also examine both established and emerging therapeutic strategies, including restoring T cell subset balance, modulating T cell–derived pro- and anti-inflammatory cytokines, and shifting macrophage polarization driven by pro-inflammatory T cells, to offer critical insights for future clinical intervention. T cell subset imbalance is a core driver of the progression of T2DM and its complications, and targeting T cell dysregulation represents a promising frontier in T2DM therapy.